A repatriação de refugiados afegãos: do Paquistão ao leste do Afeganistão - Candido, Mônica Tse [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The repatriation of Afghan refugees since 2002 was the main operation of this kind in United Nations High Commissioner for Refugees’ (UNHCR) history. Considering this, the present studies discuss the voluntary repatriation programme from 2002 until 2013, as well as the durable solutions model implemented by UNHCR of local integration, resettlement and repatriation. Moreover, it presents the causes of displacement of these refugees to Pakistan, main country of asylum, and the conditions of return to the Eastern region of Afghanistan, bordering area with Pakistan. After return, the main challenges faced by returnees for reintegration in the country of origin are identified and the perspectives from 2014 on, considering the political transition context that Afghanistan is going through.

A repatriação de refugiados afegãos a partir de 2002 foi a maior operação da espécie na história do Alto Comissariado das Nações Unidas para Refugiados (ACNUR). Diante disso, o presente estudo discute o programa de repatriação voluntária de 2002 a 2013 e o modelo de soluções duradouras implementado pelo ACNUR de integração local, reassentamento e repatriação. Ademais são discutidas as causas de deslocamento desses refugiados para o Paquistão, principal país de refúgio, e as condições de retorno desses indivíduos a região leste do Afeganistão, fronteira com o Paquistão. Após o retorno dos refugiados, são identificados os principais desafios para reintegração no país de origem enfrentados pelos retornados e as perspectivas a partir de 2014 diante da transição política por que passa o Afeganistão.
Keywords: Nações Unidas Alto Comissariado para Refugiados; Estrangeiros - Paquistão - Séc. XXI; Refugiados - Afeganistão - Séc. XXI; Afeganistão - História - 2001-; Refugees